2021
DOI: 10.1111/cmi.13328
|View full text |Cite
|
Sign up to set email alerts
|

Annulate lamellae and intracellular pathogens

Abstract: Annulate lamellae (AL) have been observed many times over the years on electron micrographs of rapidly dividing cells, but little is known about these unusual organelles consisting of stacked sheets of endoplasmic reticulum-derived membranes with nuclear pore complexes (NPCs). Evidence is growing for a role of AL in viral infection. AL have been observed early in the life cycles of the hepatitis C virus (HCV) and, more recently, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), suggesting a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…We then sought to determine if HCV core retrieves Nup98 alone or in combination with other proteins from the nuclear pore complex (NPC) or, alternatively, from annulate lamella (AL) pore complex (ALPC). The latter structures are discrete cytosolic double-membrane structures containing most components of the NPC, with the exception of some Nups such as TPR (also known as Megator/Mtor), a nuclear basket protein ( 10 ), and were identified in close proximity to HCV replication organelles ( 12 ). While these structures have mainly been identified by electron microscopy ( 22 ), recent studies indicated that RanBP2 (also known as Nup358) is a major constituent of ALPC ( 10 , 23 ), together with Nup98 ( 10 ), and that cytoplasmic RanBP2 staining could be considered a reliable AL marker ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We then sought to determine if HCV core retrieves Nup98 alone or in combination with other proteins from the nuclear pore complex (NPC) or, alternatively, from annulate lamella (AL) pore complex (ALPC). The latter structures are discrete cytosolic double-membrane structures containing most components of the NPC, with the exception of some Nups such as TPR (also known as Megator/Mtor), a nuclear basket protein ( 10 ), and were identified in close proximity to HCV replication organelles ( 12 ). While these structures have mainly been identified by electron microscopy ( 22 ), recent studies indicated that RanBP2 (also known as Nup358) is a major constituent of ALPC ( 10 , 23 ), together with Nup98 ( 10 ), and that cytoplasmic RanBP2 staining could be considered a reliable AL marker ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, recent studies have shed light on AL composition ( 10 , 23 , 24 ), allowing us to detect them by fluorescence microscopy. The number of AL seems to be increased upon infection by several viruses, including hepatitis A virus ( 48 ), Japanese encephalitis virus ( 49 ), and SARS-CoV-2 ( 50 ), or appears to localize at close proximity to remodeled membranes induced by HCV ( 12 ); yet, their precise role was not characterized in these studies. It has also been proposed that AL could represent storage vesicles for viral glycoproteins in the case of human herpesvirus 6 ( 51 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The synthesis of approximately one-third of all cellular proteins is governed in this organelle [ 58 ]. As obligate parasites that solely rely on host machineries to thrive and produce progeny virions, almost all viruses usurp the endogenous functions of numerous ER-resident channels, chaperones, and enzymes throughout the whole viral life cycle [ 60 , 61 , 62 , 63 ]. Confocal imaging revealed that the overexpressed non-structural polyprotein pORF1 predominately co-localized with ER marker BAP31 [ 64 ], indicating that ER is likely to be a central organelle that governs HEV replication.…”
Section: Cellular Organelles and Proteins Involved In Hev Translation And Replicationmentioning
confidence: 99%
“…Many functions for AL have been proposed based on electron microscopic observations, which include roles in infection, cancers, gene expression, mRNA regulation and development (Kessel, 1992). AL are remodelled extensively during embryonic development, infection by intracellular pathogens including SARS-CoV-2 and in cancers (Eymieux et al, 2021;Kessel, 1992). Recently, involvement of AL in functional assembly of NPCs has been reported (Hampoelz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%